Synthesis of N-alkyl-and N,N-dialkyl-N'-acyl- and N'-aroythioureas, and aspects of their co-ordination chemistry with Pt(II)and Pd(II) - Miller, Jörn Derrick Schuster (Department of Chemistry, 2014)
Includes bibliographical references.